Polymodal TRPV1 and TRPV4 Sensors Colocalize but Do Not Functionally Interact in a Subpopulation of Mouse Retinal Ganglion Cells - Lakk, Monika; Young, Derek; Baumann, Jackson M.; Jo, Andrew O.; Hu, Hongzhen; Križaj, David (Frontiers in Cellular Neuroscience, 2018)
Retinal ganglion cells (RGCs) are projection neurons that transmit the visual signal from the retina to the brain. Their excitability and survival can be strongly influenced by mechanical stressors, temperature, lipid metabolites and inflammatory mediators but the transduction mechanisms for these non-synaptic sensory inputs are not well characterized. Here, we investigate the distribution, functional expression and localization of two polymodal transducers of mechanical, lipid and inflammatory signals, TRPV1 and TRPV4 cation channels, in mouse RGCs. The most abundant vanilloid mRNA species was Trpv4, followed by Trpv2 and residual expression of Trpv3 and Trpv1. Immunohistochemical and functional analyses showed TRPV1 and TRPV4 channels are expressed as separate molecular entities, with TRPV1-only (~10%), TRPV4-only (~40%) and TRPV1+TRPV4 (~10%) expressing RGC subpopulations. The TRPV1+TRPV4 cohort included SMI-32-immunopositive alpha RGCs, suggesting potential roles for polymodal signal transduction in modulation of fast visual signaling. Arguing against obligatory heteromerization, optical imaging showed that activation and desensitization of TRPV1 and TRPV4 responses evoked by capsaicin and GSK1016790A are independent of each other. Overall, these data predict that RGC subpopulations will be differentially sensitive to mechanical and inflammatory stressors.